Prácticas laborales inclusivas en la actividad física (2022)
In physical education, students acquire higher levels of performance and behaviors necessary for the systematic practice of physical activity. For this, it is necessary to have an updated physical culture professional who is prepared to face the difficulties that students may present during classes. In Cuba, these teachers currently face an outdated teaching program, since the rigidity of its contents does not allow working with the diversity that exists in regular education. The research entitled “Inclusive labor practices in physical activity”, whose objective was to promote work with diversity in the preparation of the future professional, shows the reader how the cooperative learning strategy helps in the preparation of future physical culture professionals to work with the diversity of children their classes.